Pengaruh Model Pembelajaran Reciprocal Teaching terhadap Keaktifan Belajar Peserta Didik Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP Negeri 2 Pollung Tahun Pembelajaran 2023/2024 - Kartika Marbun; Baginda Sitompul; Tahadodo Waruwu (Jurnal Magistra, 2024)
The aim of this research is to find out whether there is a difference in the learning activity of students who use the reciprocal teaching model compared to conventional ones in class VIII Christian Religious Education and Character education at SMP Negeri 2 Pollung for the 2023/2024 academic year. The research hypothesis is: "The Reciprocal Teaching Model has a positive and significant effect on the Learning Activeness of Christian Religious Education and Character Education Students in Class VIII of SMP Negeri 2 Pollung for the 2023/2024 Academic Year." The population is all students who are Protestant Christians in Class VIII of SMP Negeri 2 Pollung which consists of 6 classes totaling 180 students. The research sample was determined using the Purposive Sampling technique, namely 30 students in class VIII5 as the experimental class which used the reciprocal teaching model and 30 students in class VIII4 as the control class which used ordinary treatment (conventional class). This research method is the Quasi Experimental Design method using a Nonequivalent Control Design. The instrument used in this research was a test with 30 items. Research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score). It was found that the average value for the experimental class was 0.6370 in the medium category, while the average value for the control class was 0.2531. in the low category so it is known that increasing the Learning Activeness of Class VIII Christian Religious Education and Character Education students at SMP Negeri 2 Pollung for the 2023/2024 academic year is more effective using the Reciprocal Teaching model than using conventional treatment. Then carrying out an independent test using the t test obtained a value of t = 7.040 > t table (α = 0.05; df = 58) = 2,000. Thus, it can be concluded that the research hypothesis is accepted, namely that there is a difference in the learning activity of students before and after learning with the Reciprocal Teaching Model in Learning Christian Religious Education and Character Education for Class VIII SMP Negeri 2 Pollung for the 2023/2024 Academic Year and H0 is rejected.